Intervención educativa con elementos de Educación Popular en Salud para prevenir la picadura de alacrán - Yañez Santaolalla, Jair; Betanzos Reyes, Ángel Francisco; Lara López, Luz María (Horizonte Sanitario, 2022)
Objective: To evaluate implementation of an educational initiative withelements of Popular Health Education on empowerment and changes in healthfor prevention of scorpion stings, in women from municipality of Tetecala,Morelos.Material and methods: Educational initiative was carried out in womenassigned to PROSPERA program, with 16 participants. It consisted of 5 weeklysessions, with a time of approximately 2 hours each. A diagnosis was made onthe knowledge and causes of the scorpion sting, with this information the maincomponents of educational strategy were designed (1. Knowledge of scorpion;2. Risks for scorpion sting; 3. Prevention of scorpion sting). It was carried outin the months of February and March 2019. Two categories, empowerment andchanges in health, were evaluated, delving into elements described by NoelleWiggins, using a mixed methodology. The measurements were made to thesame group before and after educational initiative. Qualitative evaluation wascarried out by analyzing ethnographic record. Quantitative part was appliedquestionnaire on knowledge and practices.Results: Changes in elements of empowerment were identified, as well aschanges in health.Conclusions: Using elements of Popular Health Education has similar effectsthan strategies where pure methodology is used. In the prevention of scorpionstings, it showed similar results to other health problems.Keywords: Scorpion stings; Health Education; Health Promotion;Empowerment.